Türkiye’de ticaret ve sanayi odalarının tarihsel gelişimi (1880-1952) - Koraltürk, Murat (My University, 1999)
Bu tezde Osmanlı ve Cumhuriyet döneminde ticaret ve sanayi odalarının gelişimi anlatılmaktadır. Tez Osmanlı ve Cumhuriyet dönemi kaynaklarının sonuçlarına dayanmaktadır. Tezle modern bir toplumun gelişiminde ticaret ve sanayi odalarının rolü ortaya konmaktadır.

Historical development of Chambers of Commerce and Industry in Turkey (1880-1952) This thesis describes historical development of Chambers of Commerce and Industry in Ottoman and Republic period. It is result of an intensive review of Ottoman and Republic written resources. Thesis indicates the role Chambers of Commerce and Industry in development a modern community.
Keywords: Ticaret odaları